Identifying and prioritizing key success indicators in building projects - MOHAMMAD JAVAD abdolahi; behnood barmayevar; Taimoor marjani; Reaza esmaeilabadi (مهندسی و مدیریت ساخت)
The abstract should state briefly the purpose of the managers and people involved in the project is the success of the project, and on the other hand, success is a general concept, so the purpose of this research is to identify the success indicators of the project. Since the success indicators are different for different projects, and This issue in construction projects has more differences than other industries due to the extent of this industry, so the focus of the current research is only on construction projects. This research is based on the result of an applied research and based on how to obtain the required data, it is considered a survey research. The process of doing the work is as follows, in order to identify the relevant indicators, first by reviewing related domestic and foreign articles and then interviewing experts, the key indicators of the success of construction projects were identified, and then the aforementioned indicators were prioritized through a survey through a questionnaire. became It is worth mentioning that in order to achieve a complete point of view, the statistical population of this research includes 52 experts with sufficient experience who are present in various elements of construction projects (contractors, consultants and employers). According to the results of the survey, 6 key indicators for the success of construction projects were obtained.